Perceptions of Tobacco Product-Specific COVID-19 Risk and Changes in Tobacco Use Behaviors Among Smokers, E-Cigarette Users, and Dual Users. Issue 9 (29th March 2021) - White, Augustus M; Li, Dongmei; Snell, L Morgan; O'Connor, Richard; Hoetger, Cosima; Croft, Daniel; Lester, Rebecca C; McIntosh, Scott; Underwood, Megan; Schneller, Liane; Breland, Alison; Barnes, Andrew J; et al.
Abstract: Introduction: Coronavirus Disease 2019 (COVID-19) is a public health crisis, but its effects on tobacco users remain ill-defined. This report aimed to assess the relationship between tobacco product-specific risk perceptions for COVID-19 and changes in tobacco use since the start of the pandemic. Methods: A sample (n = 776) of past-30 day exclusive smokers (n = 238), exclusive e-cigarette users (n = 143), and dual users (n = 395) residing in the US and aged 18 or older were collected using Mechanical Turk from April 27 to June 8, 2020. Adjusted associations between tobacco product-specific COVID-19 risk perceptions (ie risk that smokers/vapers are at for COVID-19 relative to non-smokers/non-vapers) and changes in tobacco use since the pandemic began were assessed using partial proportional odds models. Results: A majority of those who used cigarettes (63.7%) and e-cigarettes (56.1%) felt that the risk of COVID-19 was greater for users of their tobacco product than for non-users. Twenty-four percent of smokers had increased their cigarette use since the start of the pandemic and 28.0% had decreased. Similarly, 27.3% of e-cigarette users had increased their e-cigarette use since the start of the pandemic and 23.8% had decreased. Higher risk perceptions for COVID-19 were associated with reductions in tobacco use since the pandemic began for exclusive e-cigarette users and dual users. Conclusions: These findings provide the support that tobacco product-specific COVID-19 risk perceptions may be an important correlate of changes in tobacco use during the pandemic. Targeted information to inform tobacco users regarding their risks for COVID-19 is needed during this public health crisis. Implications: Few published studies have investigated the relationship between tobacco product-specific risk perceptions for COVID-19 and changes in tobacco product use since the pandemic began. This study enhances the current literature by providing evidence that higher tobacco product-specific risk perceptions for COVID-19 are associated with reductions in tobacco use since the pandemic began for exclusive e-cigarette users and dual users of cigarettes and e-cigarettes. Additionally, daily tobacco users may be more likely to have increased their tobacco use than non-daily users. These findings emphasize the importance of disseminating targeted health information to tobacco users regarding COVID-19 risks.